PERENCANAAN PEMBERDAYAAN PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI DALAM RANGKA KETERBUKAAN INFORMASI PUBLIK - Yuliany, Leny (FIA UB, 2013)
Abstract: Empowerment of Information Management Planning Officers and Documentation for a Public Disclosure. Bureaucracy reformation which is being implemented in Indonesia covers many realms, one of them is transperancy. The existance of Law No. 14/2008 (UU KIP) becomes a hope of transparency in governmental functioning in Indonesia. This paper aims to describe the planning of the empowerment of Documentation and Information Management Officer (PPID)of Bantul Regency in the framework of KIP and the supporting and constraining factors in the plannning. Research method is descriptive qualitative. The planning of the PPID empowerment in the framework of KIP in Bantul Regency has not formulated optimally. Supporting factors are regulations, IT infrastructure, budget, NGO, and the existance of Information Commission of DIY Province. Constraining factors are the absence of detail indicators of planning target, weak coordination, lack of socialization, human resources, , and the weak implementation of KIP by local governments in DIY. Keywords: planning, PPID, empowerment, transperancy Abstrak: Perencanaan Pemberdayaan Pejabat Pengelola Informasi dan Dokumentasi Dalam Rangka Keterbukaan Informasi Publik. Reformasi birokrasi yang sedang dijalankan di Indonesia meliputi berbagai bidang, salah satunya transparansi. Hadirnya UU KIP menjadi harapan tegaknya transparansi dalam penyelenggaraan pemerintahan di Indonesia. Tulisan ini bertujuan mendeskripsikan perencanaan pemberdayaan PPID Kabupaten Bantul dalam rangka KIP dan faktor-faktor pendukung serta penghambat dalam perencanaan pemberdayaan PPID. Metode penelitian menggunakan deskrpitif kualitatif. Perencanaan pemberdayaan PPID dalam rangka KIP di Kabupaten Bantul belum dirumuskan secara optimal. Faktor pendukung: regulasi, infrastruktur Teknologi Informasi, anggaran, LSM, dan Komisi Informasi Provinsi DIY. Faktor penghambat: perencanaan belum memiliki indikator target yang jelas, lemahnya koordinasi, kurangnya sosialisasi, SDM, dan lemahnya implementasi KIP oleh pemerintahan setingkat di DIY. Kata kunci: Perencanaan, PPID, transparansi